Comparative proteomics analysis of human and ruminant milk serum reveals variation in protection and nutrition. (30th September 2018) - Lu, Jing; Zhang, Shuwen; Liu, Lu; Pang, Xiaoyang; Ma, Changlu; Jiang, Shilong; Lv, Jiaping
Highlights: Large variations in protein composition were observed between human and ruminant milk. Human milk provides precise protection, nutrients as well as bioactive components to guarantee the growth of newborns. Human milk serum contained higher concentration of mucosal immune response proteins, complement proteins and regulators. The concentration of bactericidal proteins were relatively higher in ruminants milk serum. Osteopontin in yak milk was enriched. Abstract: In present study, 198, 169, 213 and 128 proteins were identified and quantified in human, cow, goat and yak milk serum respectively by using proteomics techniques. Large variations were observed between human and ruminant milk proteins. Human milk contained higher concentration of mucosal immune response, complement proteins and regulators. The concentration of bactericidal proteins were relatively higher in ruminants milk. Human milk exclusively expressed proteins important for delivery or utilization of nutrients. Peptidase inhibitors prevent the bioactive proteins/peptides in human milk from gastral-intestinal digestion. Protein composition among ruminants milk was similar but with variations. Goat milk contained high level of complement proteins but low level of corresponding regulators. In addition, the acute phase proteins were significantly higher in goat milk. Of note, osteopontin in yak milk was enriched, which could offer an alternative source for producing osteopontin and revealed possible nutritional value of yak milk.